Engineering of Co3O4 electrode via Ni and Cu-doping for supercapacitor application - Worku, Ababay Ketema; Asfaw, Alemu; Ayele, Delele Worku (Frontiers in Chemistry, 2024)
Although cobalt oxides show great promise as supercapacitor electrode materials, their slow kinetics and low conductivity make them unsuitable for widespread application. We developed Ni and Cu-doped Co3O4 nanoparticles (NPs) via a simple chemical co-precipitation method without the aid of a surfactant. The samples were analyzed for their composition, function group, band gap, structure/morphology, thermal property, surface area and electrochemical property using X-ray diffraction (XRD), ICP-OES, Fourier transform infrared (FTIR) spectroscopy, Ultraviolet-visible (UV-Vis), Scanning electron microscopy (SEM), Thermogravimetric analysis (TGA) and/or Differential thermal analysis (DTA), Brunauer–Emmett–Teller (BET), and Impedance Spectroscopy (EIS), Cyclic voltammetry (CV), respectively. Notably, for the prepared sample, the addition of Cu to Co3O4 NPs results in a 11.5-fold increase in specific surface area (573.78 m2 g−1) and a decrease in charge transfer resistance. As a result, the Ni doped Co3O4 electrode exhibits a high specific capacitance of 749 F g−1, 1.75 times greater than the pristine Co3O4 electrode’s 426 F g−1. The electrode’s enhanced surface area and electronic conductivity are credited with the significant improvement in electrochemical performance. The produced Ni doped Co3O4 electrode has the potential to be employed in supercapacitor systems, as the obtained findings amply demonstrated.